A Virtual Protocol Model for Computer-Human Interaction - Nielsen, Jakob (DAIMI Report Series, 1984)
A model of computer-human interaction is presented, viewing the interaction as a hierarchy of virtual protocol dialogues. Each virtual protocol realizes the dialogue on the level above itself and is in turn supported by a lower level protocol. This model is inspired by the OSI-model for computer networks from the International Standards Organization. The virtual dialogue approach enables the separation of the technical features of new devices (e.g. a mouse or a graphical display) from the conceptual features (e.g. menus or windows). Also, it is possible to analyze error messages and other feedback as part of the different protocols.